Aicardi–Goutières syndrome harbours abundant systemic and brain-reactive autoantibodies. Issue 10 (6th June 2014) - Cuadrado, Eloy; Vanderver, Adeline; Brown, Kristy J; Sandza, Annie; Takanohashi, Asako; Jansen, Machiel H; Anink, Jasper; Herron, Brian; Orcesi, Simona; Olivieri, Ivana; Rice, Gillian I; Aronica, Eleonora; et al.
Abstract : Objectives: Aicardi–Goutières syndrome (AGS) is an autoimmune disorder that shares similarities with systemic lupus erythematous. AGS inflammatory responses specially target the cerebral white matter. However, it remains uncertain why the brain is the most affected organ, and little is known about the presence of autoantibodies in AGS. Here, we aim to profile specific autoantibodies in AGS and to determine whether these autoantibodies target cerebral epitopes. Methods: Using a multiplex microarray, we assessed the spectrum of serum autoantibodies in 56 genetically confirmed patients with AGS. We investigated the presence of immunoglobulins in AGS brain specimens using immunohistochemistry and studied the reactivity of sera against brain epitopes with proteomics. Results: Serum from patients exhibited high levels of IgGs against nuclear antigens (gP210, Nup62, PCNA, Ro/SSA, Sm/RNP complex, SS-A/SS-B), components of the basement membrane (entactin, laminin), fibrinogen IV and gliadin. Upon testing whether antibodies in AGS could be found in the central nervous system, IgGs were identified to target in vivo endothelial cells in vivo and astrocytes in brain sections of deceased patients with AGS. Using a proteomics approach, we were able to confirm that IgGs in serum samples from AGS patients bind epitopes present in the cerebral white matter. Conclusions: Patients with AGS produce a broad spectrum of autoantibodies unique from other autoimmune diseases. Some of these autoantibodies target endothelial cells and astrocytes in the brain of the affected patients, perhaps explaining the prominence of neurological disease in the AGS phenotype.